The war extension rhetoric an analogic criticism of U.S. Presidential rhetoric during the Iraq and Philippine-American wars - Lambino, Antonio II (2011)
Studies on U.S. Presidential war rhetoric tend to ignore the dimension of time, i.e., most focus analysis on the inception of war. In reality, however, many wars are protracted and may last beyond initial public expectations. War messages are therefore employed not only to seek congressional and public support for the inception, but also for the extension of armed conflict abroad. Using the methodology of analogic criticism, this study provides seminal ideas for what calls the "war rhetoric of extensions." By comparing Bush's speeches during the current Iraq War and McKinley/Roosevelt's annual messages during the Philippine-American War, this paper argues that the war rhetoric of extension has the following characteristics: similar patterns of argumentation, epideictic statements that elevate American prestige, and paternalistic language.
Keywords: Rhetoric -- Political aspects -- United States; Political oratory -- United States -- History; Presidents -- United States -- Language